Neurotherapeutic effects of curcumin on lead-induced toxicity in a rat model with emphasis on cerebellar damage - Kabeer, Abubakar (2019)
Lead (Pb) is a toxic environmental heavy metal that induces serious clinical defect on all organs with the brain, kidney and liver being the primary targets, hence Pb poisoning has been a major threat to public health in developing countries due to human activities. Curcumin is the main active constituent of turmeric rhizome (Curcuma longa) with great neuroprotective role as well as being a strong antioxidant and anti-inflammatory properties. This study is aimed at evaluating the therapeutic potentials of curcumin on Pb-induced toxicity in a rat model since the application of chelation therapy is associated with numerous side effects. Thirty-six male Sprague Dawley rats aged 8 weeks weighing between 200 – 250 g were randomly assigned into five (5) groups with 12 rats in Group A (normal saline) and 6 rats each for Group B (LTG) (50 mg/kg of lead acetate for 4 weeks), Group C (RC) (50 mg/kg lead acetate for 4 weeks and left for another 4 weeks without treatment), Group D (Cur100) (50 mg/kg lead acetate for 4 weeks, followed by 100 mg/kg curcumin for 4 weeks) and Group E (Cur200) (50 mg/kg lead acetate, followed by 200 mg/kg curcumin for 4 weeks). All experimental groups received the oral treatment through orogastric-tube on alternate days. Motor functions was assessed using horizontal bar method while Pb concentration in the cerebellum, liver and kidney of the rats were evaluated using inductive coupled plasma mass spectrometry (ICP-MS) techniques. Further, the rats’ cerebellum, liver and kidney were fixed in 10% buffered formalin for 5 days and subsequently prepared for histological examination using paraffin method. The Pbadministered rats showed significant decrease in motor activity scores, SOD activity with increase MDA levels and Pb concentration in their cerebellum, liver, kidney and serum with marked alterations in the histological architecture of the cerebellum, liver and kidney. However, treatment with curcumin improved their functional motor activity, reduced Pb concentration in the cerebellum, liver and kidney and ameliorates the markers of oxidative stress as well as attenuating the alterations in the histological architecture of the cerebellum, liver and kidney. Therefore, it is concluded that curcumin attenuates Pb-induced toxicity via inhibition of oxidative stress and chelating activity in rats.